Main findings and diagnostic yield of bronchoalveolar lavage, bronchial brushing and transbronchial biopsy in HIV-positive patients - dos Santos, João Paulo Vieira (Rev Inst Med Trop Sao Paulo, 2019)
Bronchoalveolar lavage, bronchial brushing and transbronchial biopsy are of fundamental importance in the diagnosis of pathologies affecting the lungs of immunosuppressed patients, especially those infected with HIV. This was a descriptive and retrospective study, in which the results of bronchoalveolar lavages, bronchial brushings and transbronchial biopsies of HIV-positive patients attended at the Clinical Hospital of the Federal University of Triangulo Mineiro from 1999 to 2015 were reviewed to determine the most frequent findings in these patients, to evaluate the diagnostic accuracy of these procedures and to correlate bronchoscopy results with clinical and radiological findings. Serological tests for HIV were confirmed and cases with negative or unverified serology were excluded. Medical records were reviewed for correlation with clinical and radiological findings. A total of 1,423 patients with a mean age of 50 years were initially selected; 727 cases had no serology for HIV; 696 had serology for HIV and 64 were positive. Of these, 47 were men, aged 24 to 84 years, and 17 women, aged 31 to 69 years. Biopsies and cytological tests were positive in 20 (31.25%) of the 64 patients and the most frequent diagnosis was pneumocystosis, found in 8 cases (12.5%). Of the 20 bronchofibroscopy-positive patients, only 2 did not show agreement between histopathological and clinical-radiological diagnoses. The analysis of the cytological tests and biopsy specimens obtained by bronchofibroscopy seems to be valuable for the etiological diagnosis of pulmonary infections in HIV- positive patients; however, negative results do not always exclude the diagnosis. In these cases, clinical symptoms and imaging findings may help to guide the best therapy.